Leaf anatomy of four endemic species of the Cladocolea-Struthanthus complex (Loranthaceae) from Guerrero, Mexico - Hernández-Salazar, Misadai; Cerros-Tlatilpa, Rosa; Sandoval-Zapotitla, Estela; Flores-Morales, Alejandro (Phytotaxa, 2025)
The Cladocolea-Struthanthus complex was established by Kuijt (1975) due to the morphological similarities between both genera. This study analyzed the leaf anatomy of four endemic species of this complex from Guerrero, Mexico. The aim was to identify anatomical features to support taxonomic studies within the species studied. Leaf anatomy of Cladocolea kuijtii, C. molotensis, C. spathiflora and S. racemosus was compared from transverse leaf sections. The cuticle is generally smooth and fimbriate. The epidermis is one-layered, occasionally with trichomes in C. kuijtii and C. molotensis. All analyzed species are amphistomatic and isobilateral, consisting of palisade parenchyma. The sclerenchyma is represented by brachysclereids, cristarque cells and astrosclereids. Crystals such as prism and druses were observed. In Cladocolea spathiflora, crystal sand is reported for the first time in Loranthaceae. A dichotomous key was constructed using anatomical characters to assist recognition of endemic Cladocolea and Struthanthus species. The taxonomic importance of these characters is discussed for the complex and for the family.